Preparation, characterization, and properties of chitosan films with cinnamaldehyde nanoemulsions. (December 2016) - Chen, Huanle; Hu, Xiaorong; Chen, Enmin; Wu, Shan; McClements, David Julian; Liu, Shilin; Li, Bin; Li, Yan
Abstract: Natural aldehydes, such as cinnamaldehyde, can be used to modify the properties of chitosan-based materials by covalent cross-linking the chitosan molecules. Due to the non-polarity and hydrophobicity of cinnamaldehyde, emulsification technique was used to prepare homogeneous cinnamaldehyde-chitosan films. Under optimized conditions, cinnamaldehyde nanoemulsions led to the successful fabrication of uniform and smooth chitosan films. FTIR analysis of the films indicated the formation of chitosan-cinnamaldehyde Schiff base. The cross-linked films strongly absorbed UV–visible light and inhibited the emission of fluorescent light, and may therefore provide good photo-protection. The thickness (26–61 μm) and transparency (clear to turbid) of the chitosan films were modulated by varying the aldehyde/amino group ratio. The mechanical properties and water vapor permeability of the films also depended on the amount of cinnamaldehyde nanoemulsion utilized. Chitosan films showed good antimicrobial activity, but had better antifungal than antibacterial activity. Graphical abstract: The content of cinnamaldehyde-loaded nanoemulsion modulated the surface and cross-section structure of crosslinked chitosan films. Highlights: Active chitosan films were prepared by cross-linking with cinnamaldehyde nanoemulsions. Cross-linked chitosan films showed good UV barrier properties. The surface morphology of chitosan films showed granular structure.